Allogeneic haematopoietic cell transplantation offers the chance of cure for patients with transformed follicular lymphoma - Heinzelmann, Frank; Bethge, Wolfgang Andreas; Beelen, Dietrich W.; Stelljes, Matthias; Dreger, Peter; Engelhard, Marianne; Finke, Jürgen; Kröger, Nicolaus; Holler, Ernst; Bornhäuser, Martin; Müller, Annerose; Haubitz, Imme; et al. (Journal of cancer research and clinical oncology, 2018)
PurposeIn patients with follicular lymphoma, secondary transformation to aggressive lymphoma (tFL) implies a poor prognosis. In principle, allogeneic haematopoietic cell transplantation (allo-HCT) offers a chance of cure for tFL but is rarely practiced. Aim of this retrospective multicenter study was to define the actual significance of allo-HCT in treatment of tFL.MethodsThe database of the German Registry for Stem Cell Transplantation (DRST) was screened for patients who underwent allo-HCT for tFL 1998-2008. Confirmation of tFL-diagnosis by local and/or pathologists of the National NHL Board was mandatory for enrolment. Gaps in reported EBMT Minimum Essential Data datasets (MED-A) were filled by local DRST data managers. Relevant HCT outcome variables were evaluated by uni- and multivariate statistical analysis.ResultsMedian age of enrolled 33 patients was 51 years with a post allo-HCT median follow-up of 7.1 years of surviving patients. At time of HCT 24/33 patients had chemosensitive disease. In 24/33 patients reduced intensity conditioning (RIC) was used. Estimated 1, 2, 5-year overall survival (OS) and event-free survival rates were 49/39/33, and 33/30/24%. Cumulative 100 days non-relapse mortality was 25%. Chemosensitive disease, RIC, and limited chronic GvHD were identified as independent prognostic factors for OS.ConclusionsAllo-HCT offers the chance of cure for tFL.
Gesehen am 24.09.2019